Perceptions, attitudes and emotions of adolescents facing the news of the COVID-19 (Encuentros, 2022)
The news about Covid-19 and the pandemic have had an impact on the emotions and perceptions of adolescents. This research article identifies the perceptions, emotions, and attitudes manifested by adolescents in the face of news broadcasts about Covid-19. It corresponds to a descriptive non-experimental quantitative study. A questionnaire was applied to 158 students from four educational institutions in Cúcuta (Colombia) between the ages of 14 and 20. The results show that young people use multimodal channels, mainly television and social networks to learn about Covid-19. The content consumed produces negative emotions in young people and unclear perceptions about the scope of the pandemic and its relationships with other settings. It is concluded that the mass media have helped little in the generation of positive emotions among adolescents, nor in a better perception and understanding of the phenomenon and the crisis.
Keywords: Covid-19; News; Teenagers; Perceptions; Emotions